Regulation of connexin‐ and pannexin‐based channels by post‐translational modifications. (17th July 2013) - D'hondt, Catheleyne; Iyyathurai, Jegan; Vinken, Mathieu; Rogiers, Vera; Leybaert, Luc; Himpens, Bernard; Bultynck, Geert
<x xml:space="preserve">Abstract</x> Post‐translational modifications (PTMs) affect the regulation and localisation of connexin (Cx) and pannexin (Panx) proteins, which form large conductance channels, functioning as mediators of communication between neighbouring cells via gap junction channels and/or hemichannels. Hereby, PTMs influence the assembly, trafficking and function of Cx‐ and Panx‐based channels in normal cell biology and pathophysiology. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>